The blue house I loved - Yang, Kao Kalia, 1980- (University of Minnesota Press, 2025)
"The Blue House I Loved centers on a family of newly arrived Hmong refugees who move into the lower level of a duplex in St. Paul, Minnesota. The narrator loves her aunt and uncle's home with its mismatched furniture, but it is too small for the large family. The boy cousins sleep in the three-season porch, where their wet hair freezes in wintertime, and the rest of the family crowds into two bedrooms. Yet this is the cherished home where they live and love, their own small corner of a very large and unfamiliar place, and in this blue house a young girl learns about her new country. Eventually, the family moves in search of more space, and years later the house is torn down. Where it was, green grass now grows. But for this girl and her family, the ghost of the house remains, its memories a strong thread that holds time at bay and hearts close together. Combining Kao Kalia Yang's lyrical prose with ethereal illustrations by artist and architect Jen Shin, The Blue House I Loved speaks to the multitude of refugee experiences around the world, honoring the challenges they face and the homes they create together." -- Publisher marketing